Christianity - "Bevan, Edwyn" (London, 1948)
Unknown has contributed to Christianity as an author.As a pediatrician, writer, wife, and mother, Perri Klass has demonstrated how medicine is integral to the health of families and communities, and how doctors themselves struggle to balance the conflicting needs of profession, self, and family. As medical director of Reach Out and Read, she encourages other pediatricians to foster pre-reading skills in their young patients. While earning her M.D. at Harvard, Klass contributed articles to "Mademoiselle" and "The New York Times" as well as to scientific and medical journals. She also wrote her first book, "A Not Entirely Benign Procedur
Keywords: Christianity